Comprehensive assessment of specific antibodies on infectious activity of tick-borne encephalitis virus - Leonova, G. N.; Majstrovskaya, O. S.; Lubova, V. A.; Sanina, N. B. (Infekt͡s︡ii͡a︡ i immunitet, 2019)
Vaccines for prophylactic immunization provide the most reliable and effective protection against the vast majority of infectious diseases. Tick-borne encephalitis (TBE) represents a high-priority medical issue at the territory of the Eurasian continent. Of great importance is assessing a role of distinct antibody titers especially low titers, observed quite often in vaccinated individuals, sometimes posing obstacles in determining a threshold of seropositivity as well as the level of specific protection against TBE virus. We aimed at obtaining data to assess antiviral activity of virus-specific antibodies with distinct titer levels based on the in vitro, ex vivo and in vivo experimental studies with a highly virulent Far-Eastern strain of tick-borne encephalitis virus. The in vitro, ex vivo and in vivo comprehensive experimental studies with a highly virulent Far-Eastern strain of tick-borne encephalitis virus (TBEV) were conducted and the dynamics of antiviral activity of virus-specific antibodies at variable titers (1:100–1:3200) was measured (timeframe ranged within 1–96 hours p.i.) to provide a rationale for evaluating the antiviral immune response. It was found that the in vitro experiments demonstrated that the IgG at 1:100 titer exerted a weak anti-TBEV neutralizing effect at all time-points examined. The IgG 1:400 titer caused a 2 log PFU/mL decline in TBEV Dal strain yield at 72 h post-infection, whereas at 1:3200 titer it completely suppressed TBEV replication throughout the observation period. The ex vivo experiments with blood serum obtained from vaccinated subjects demonstrating a range of TBEV antibody titers (sera from vaccinated individuals with varying anti-TBEV antibody titers) and in vivo (outinbred white mice) experiments revealed a delayed virus elimination for antibody titers at 1:100 and 1:200 as well as rapid virus elimination (1–2 days p.i.) for antibody titers greater than 1:400. Thus, antibody titer at 1:400 may be considered as the universal anti-TBEV protection threshold. In order to properly conclude regarding the revaccination schedule it is advised to start with testing blood serum for durability of anti-TBEV immune response. Subjects with TBEV antibody titers at 1:100 and 1:200 should be strongly recommended to undergo a mandatory revaccination. Such an approach is believed to be the most effective way toward enhancing efficacy of vaccine-mediated protection against TBE.